2019
DOI: 10.1093/ageing/afz164.89
|View full text |Cite
|
Sign up to set email alerts
|

89 Randomised Controlled Trial of the Effect of Tai Chi on Postural Balance of People with Dementia

Abstract: Introduction We investigated the effect of Tai Chi exercise on postural balance among people with dementia (PWD), and the feasibility of a definitive trial on falls prevention. Method We conducted a randomised controlled trial. Dyads, comprising community-dwelling PWD and their informal carer (N=85), were randomised to usual care (n=43) or usual care plus the intervention (n=42). For the intervention, over 20 weeks, Tai Chi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 55 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…The aim of this study was to explore the effects of Tai Chi on iTUG in people with dementia. Previously, it was identified that there was no significant difference in total time to complete the TUG [19] and this study adds to the understanding by demonstrating that this lack of effect is evident across all sub phases of the iTUG. This provides new comprehension, as each sub phase of the iTUG constitutes subtle or large differences in their underlying physiological constructs (i.e.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The aim of this study was to explore the effects of Tai Chi on iTUG in people with dementia. Previously, it was identified that there was no significant difference in total time to complete the TUG [19] and this study adds to the understanding by demonstrating that this lack of effect is evident across all sub phases of the iTUG. This provides new comprehension, as each sub phase of the iTUG constitutes subtle or large differences in their underlying physiological constructs (i.e.…”
Section: Discussionmentioning
confidence: 54%
“…If the Tai Chi intervention lacked the magnitude and intensity to yield any physiological change, then this could possibly explain the lack of change demonstrated in the iTUG. Fidelity of the intervention has been reported previously [19], and all participants were able to understand and follow the Tai Chi instructions. The mean supervised Tai Chi practice time was 8.4 h, which is less than half of that offered by Zou et al [35], who demonstrated significant reductions in total time to complete iTUG.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In another Cochrane review of the effects of various types of exercise on the fear of falling in older adults, it was concluded that there was no evidence that the fear of falling was reduced after the exercise was over [ 31 ]. TC has also been shown to reduce falls in people with dementia [ 32 , 33 ]. A common problem in all of these studies is that the experience of the instructor and length of time TC is used and the number of times per week is variable and, therefore, it is hard to compare some of these studies to each other [ 34 ].…”
Section: Discussionmentioning
confidence: 99%